Effect of financial management practices on effectiveness of performance contracting in service delivery of local authorities in Kenya. - Mwangi, Elliubs Kimura; Gakure, Roselyn; Arasa, Robert; Waititu, Anthony (My University, 2010)
This study was an assessment of factors influencing the effectiveness Performance Contracting from in Service Delivery in Local Authorities of Kenya.Public outcry on quality of services is not uncommon in public sector more so in Local Authorities. Despite Government’s inputs and concern and introduction of performance contracting, performance of Local Authorities on service delivery is far below expectation. It is for this reason that the current study sought to assess the factors influencing Performance Contracting in Service Delivery in Local Authorities in Kenya.Specifically, the study wished to address whether Financial Management has an influence in performance contracting.Corelational research design was used to conduct the study in 175 Local Authorities in Kenya.A sample of 18 Local Authorities was selected using a stratified sampling technique.The respondents from the Local Authorities included officers from all cadres of staff who were randomly chosen from the sampled Local Authorities.The study findings indicated that financial management practices influenced performance contracting.Specifically, the study showed that the budget variances were not investigated and rectified,revenue collection and usage was not free from political interferences and all debtors were not followed in time.The study concludes that the financial management practices of Local Authorities are poor and ineffective.It can be concluded from this study that there exists a positive significant relationship between financial management practices and performance contracting of Local Authorities.The results reveal that financial management practices are statistically significant in explaining effectiveness of performance contracting of local authorities in Kenya.The study recommends that the council should put in place measures to safeguard the independence and effectiveness of internal audit departments as such department is crucial in the implementation of internal controls
Keywords: Financial Management Practices; Performance Contracting; Local Authority